2020
DOI: 10.1002/ece3.5828
|View full text |Cite
|
Sign up to set email alerts
|

Modular chromosome rearrangements reveal parallel and nonparallel adaptation in a marine fish

Abstract: Genomic architecture and standing variation can play a key role in ecological adaptation and contribute to the predictability of evolution. In Atlantic cod (Gadus morhua), four large chromosomal rearrangements have been associated with ecological gradients and migratory behavior in regional analyses. However, the degree of parallelism, the extent of independent inheritance, and functional distinctiveness of these rearrangements remain poorly understood. Here, we use a 12K single nucleotide polymorphism (SNP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 77 publications
(95 reference statements)
3
38
0
Order By: Relevance
“…This is consistent with previous studies in humans showing that CNVs contribute to higher genetic divergence than SNPs (Levy et al, 2007;Pang et al, 2010;Sudmant et al, 2015). Furthermore, recent studies in marine fishes also showed that reduced genomic regions involving structural variants account for higher genetic divergence than widely distributed SNPs (Berg et al, 2016;Barth et al 2019;Kess et al, 2020). Several hypotheses may explain this pattern.…”
Section: Cnvs Reveal a Stronger Genetic Structure Than Snpssupporting
confidence: 90%
“…This is consistent with previous studies in humans showing that CNVs contribute to higher genetic divergence than SNPs (Levy et al, 2007;Pang et al, 2010;Sudmant et al, 2015). Furthermore, recent studies in marine fishes also showed that reduced genomic regions involving structural variants account for higher genetic divergence than widely distributed SNPs (Berg et al, 2016;Barth et al 2019;Kess et al, 2020). Several hypotheses may explain this pattern.…”
Section: Cnvs Reveal a Stronger Genetic Structure Than Snpssupporting
confidence: 90%
“…2019; Kess et al. 2020). The genomic breadth and magnitude of allele frequency differentiation (i.e., near fixation of opposite alleles across Mb‐scale regions against an almost complete absence of genome‐wide differentiation, as seen in the southern part of the range) represents, to our knowledge, one of the most extreme examples reported to date of the degree to which differentiation of locally adapted populations can vary across the genome (compare to other notable examples in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This difference in structure is consistent with previous studies in humans showing that CNVs contribute to higher genetic divergence than SNPs (Levy et al., 2007; Pang et al., 2010; Sudmant et al., 2015). Furthermore, recent studies in marine fishes also showed that genomic regions including structural variants account for higher genetic divergence than SNPs that are distributed across the whole genome (Barth et al., 2019; Berg et al., 2016; Cayuela et al., 2020; Kess et al, 2020). Several hypotheses may explain this pattern.…”
Section: Discussionmentioning
confidence: 99%